2017
DOI: 10.1155/2017/5784759
|View full text |Cite
|
Sign up to set email alerts
|

Antiglycemic Effect of Water Extractable Arabinoxylan from Wheat Aleurone and Bran

Abstract: The studies on the effects of arabinoxylan (AX) polysaccharides on postprandial glucose response have resulted in contrasting results owing to the diversity in AX structures. Four water extractable AX (WEAX) extracts obtained from wheat aleurone and bran were used to investigate (a) the effect of AX on activities of α-amylase and α-glucosidase, (b) influence of AX chemical composition on their inhibition potency, and (c) kinetics of enzyme inhibition. α-Amylase activity was not significantly affected by the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…The lack of significant difference in the in vitro digestibility profiles of waffles suggest that BG does not affect amylase activity in the gastrointestinal tract as hypothesized previously. This finding is consistent with a previous study with a different soluble fiber, arabinoxylan, where amylolysis of starch was not affected by addition of arabinoxylan in vitro (23).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The lack of significant difference in the in vitro digestibility profiles of waffles suggest that BG does not affect amylase activity in the gastrointestinal tract as hypothesized previously. This finding is consistent with a previous study with a different soluble fiber, arabinoxylan, where amylolysis of starch was not affected by addition of arabinoxylan in vitro (23).…”
Section: Discussionsupporting
confidence: 93%
“…The results indicated that brush border α-glucosidase activity was not affected by BG regardless of BG's molecular weight or concentration. Similarly, arabinoxylan obtained from wheat could only inhibit α-glucosidase activity when feruloylated (23). This further suggests that viscosity of digesta generated by soluble fiber may not influence the digestibility of carbohydrates.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, the total phenolic acid content in cereal grains (a major source of dietary carbohydrates) varies from 520 to 2,792 µg/g (Ndolo & Beta, ). However, <10% of the total phenolic acids in cereals are bioaccessible and not all bound phenolic acid can inhibit intestinal α‐glucosidase activity (Malunga & Izydorczyk, ) making it hard to achieve potency levels through dietary intake. Hence, technologies that increase bioaccessibility of phenolic acids could play a major role in improving antidiabetic properties of cereal grains.…”
Section: Resultsmentioning
confidence: 99%
“…Alongside cellulose, arabinoxylan (AX) is an abundant fibre in BSG. Arabinoxylan and arabinoxylanoligosaccharides (AXOS) from other cereal sources, primarily wheat, have been shown to be linked to potential health benefits, such as modulation of glycaemic index and potential prebiotic capacity [8][9][10][11]. Both EFSA and the FDA allow claims on AX in relation to modulating the glycaemic response; EFSA restricts this claim to wheat AX while the FDA does not [12,13].…”
Section: Introductionmentioning
confidence: 99%